Trends in neurovascular surgery - Tsukahara, Tetsuya; SpringerLink (Online service). (Wein New York Springer, 2011)
The contributions in this book were presented at the fifth European-Japanese Joint Conference for Stroke Surgery, held in July 2010 in Duesseldorf, Germany. The topics treated are the management of cerebral and ventricular hemorrhage, extra-intracranial bypass surgery, surgical and endovascular treatment of cervical and intracranial arterial occlusive disease, and embolization and microsurgery of AVM and dural AV-fistulas.
Electronic reproduction.
Keywords: Central Nervous System -- Surgery; Neurovascular diseases -- Surgery; Brain -- Hemorrhage; Intracerebral hematoma; Subarachnoid hemorrhage; Electronic books